4x+1+3x=-3

Simple and best practice solution for 4x+1+3x=-3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4x+1+3x=-3 equation:


Simplifying
4x + 1 + 3x = -3

Reorder the terms:
1 + 4x + 3x = -3

Combine like terms: 4x + 3x = 7x
1 + 7x = -3

Solving
1 + 7x = -3

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-1' to each side of the equation.
1 + -1 + 7x = -3 + -1

Combine like terms: 1 + -1 = 0
0 + 7x = -3 + -1
7x = -3 + -1

Combine like terms: -3 + -1 = -4
7x = -4

Divide each side by '7'.
x = -0.5714285714

Simplifying
x = -0.5714285714

See similar equations:

| 2x^2+3+3=-7x | | Y=2x+(-8) | | -15x+9=17-x | | 4X-8=3(2X-4) | | 75+2x=15 | | X+2=2overy-1 | | +t/12=-3 | | -6b+28=9b-2 | | 3x-9=4x-24 | | 3(4x+1)=3+12x-3 | | 36+2y-15=12y-9-5y | | 8-4+2R-4R+8R= | | 2L+2W=W+84 | | 8-r=3r-14 | | x-1b=72 | | .666h-9=6-.666h | | 8x+6y-10=0 | | 24b+4=52 | | (x-3)(x-4)-(x+4)=0 | | 2n^3-24n^2-23048n=0 | | 4.3+7.5=5.8 | | 10v^2=11v+6 | | -3-10=-46 | | -(12+2r)-(r+8)=-7r+3r | | 10U-2U= | | 6x^2-13x+4= | | 4.29b-0.692=11.749 | | 3[2(5x-7)-3(4x-6)]-4[5(x-1)-7x]=6[-4(x+2)+7x] | | 6+5(8w-9)= | | 36=2L+W | | 1w+5=4 | | 3-2(x-4)=2x-5 |

Equations solver categories